Location of Interface Bose-Einstein Condensate Mixtures in Finite Space Under Neumann Boundary Condition - Quyet, Hoang Van (VNU Journal of Science: Mathematics - Physics, 2024)
In this work we proposed a simple method to determine the coordinate of interface of two-component Bose-Einstein condensates (BECs) in double parabola approximation (DPA) under Neumann boundary conditions. Based on this idea, the static properties of BECs have been investigated totally in DPA.